Surface wave scattering analysis in an initially stressed stratified media. Issue 8 (15th July 2021) - Mandi, Anand; Kundu, Santimoy; Pal, Prakash Chandra
Abstract : Design/methodology/approach: The present discussed problem deals with the torsional surface wave scattering in an initially stressed inhomogeneous medium. The assumed model consists of tri-mediums resting over a viscoelastic semi-infinite medium and the considered tri-mediums are transversely isotropic, porous, and heterogeneous respectively under the impression of initial stress. Design/methodology/approach: Heterogeneities are associated with density and rigidity in the intermediate layer and considered heterogeneities are of the trigonometric form. Displacement components are derived for mediums by applying separable variables. Findings: Frequency equation is deduced by using suitable boundary conditions, defined at the free surface of the uppermost medium, and on the interfaces between mediums. The derived equation is of the complex form, real and imaginary parts direct the phase/damped velocities respectively. Additional results are considered in particular cases. Numerical examples are adopted for computing frequency equation and drawn consequences are demonstrated graphically to analyze the significant impact of various parameters on the phase velocity as well as on damped velocity of the surface wave sketched against the wavenumber. Originality/Value: This presented research work provides a different view over the analysis of torsional surface waves than the earlier investigations. Previously studied problems on the wave generation were conducted in different models under the various affecting parameters. Study on torsional wave generation in the present model is not carried out till now. This study may find its virtue in the theoretical aspect as well as in the possible practical implications. The outcomes are relevant to geology and allied areas; moreover, the concern applications may be implicated in geological exploration, civil engineering, and prediction of Earthquake etc.